Rationalization: The Critical Link in the Fraud Chain - New Insights from Empirical Analysis of the Diamond of Fraud - Matei (Pana), Mirela; Bulau, Carmen Mihaela (Acta Universitatis Danubius. Œconomica, 2024)
Introduction: Fraud is a widespread problem that causes significant financial and reputational damage. The Fraud Diamond theory proposes four key elements that enable fraudulent behavior: pressure, opportunity, rationalization, and capability (Wolfe & Hermanson, 2004). However, little empirical research has tested the relationships between these elements. This study aims to address this gap. Methods: A questionnaire was designed to measure the four Fraud Diamond items on 5-point Likert scales. It was distributed to a sample of 120 individuals via Google forms. Cronbach’s alpha=0.81. Pearson correlations were then calculated to analyze relationships between items. Result: Factor analysis supported a four-factor structure corresponding to the Fraud Diamond items. All factors had strong reliability (α > 0.8). Rationalization showed significant positive correlations with all other items (r = .31 to .57, p < .01), whereas the other items were less consistently correlated. Discussion: The findings provide empirical support for Fraud Diamond as a framework. Rationalization can be particularly important because it facilitates the other three elements. Interventions targeting rationalization mechanisms, such as cognitive biases, could help reduce fraudulent behavior. However, the model requires further validation in different contexts. Conclusion: In summary, this study developed a valid measurement scale for the Fraud Diamond items and found rationalization to be most strongly related to the other fraud items. Reducing rationing may be a promising avenue for fraud prevention. Future research should continue to empirically test fraud theories and continue the measurement instrument development process.